The Prioritization of Kermanshah Tourism Poles Based on the Potential of Tourism Sample Regions Using TOPSIS Multi-Criteria Decision-Making Techniques - Gholamreza Noori; Samad Fotohi; Zahra Taghizadeh (جغرافیا و پایداری محیط)
Tourism sample regions as the subset of tourism poles are one of the most important and considerable issues in the tourism industry. In fact, the development of tourism sample regions will lead to the development and expansion of tourism poles. The Present study is an applied–developmental research which aims to rank the tourism poles of Kermanshah Province. Adapting a descriptive - analytical and survey methodology, the study has utilized questionnaire as research instrument. At first, using Delphi technique, 10 indexes were determined for assessment of the sample regions. Then, the data from the questionnaires were examined through TOPSIS multi-criteria decision-making techniques and the tourism poles were prioritized. According to these prioritizations, the tourism sample regions in Kermanshah pole with 0/9448 were in a very good level in comparison to other regions, and the sample regions in Hewraman pole with 0/42981 were located in the second place and in a moderate level, and other regions were assessed in the next level. The results of the present study, on the one hand, have an important contribution to the management decisions; and on the other hand, help the investors for investment and tourists for the choice of the tourism destinations.